Response of Myrtus communis Seedlings under Irrigation Frequencies - Iakovoglou, Valasia; Kokkinou, Evmorfili (International Journal of Bio-resource and Stress Management, 2018)
Nowadays the impacts of climate change are more abrupt. Semi arid Mediterranean ecosystems like Greece are characterized by frequent and intense drought events that, in conjunction with reduced water availability particularly during summer, pose obstacles to restoration efforts. The aim of this study was to investigate the growth of Myrtus communis L. seedlings under three irrigation frequencies: watering once every two weeks, once every week and three times every week for the experimental period of two months. A number of morphological variables were evaluated in addition to root growth potential and the seedlings’ dry weights for the first and the second month of the experiment. According to the results, the species was able to maintain its normal growth condition for a period of one month, even under the least irrigation frequency of one watering every two weeks. However, by the end of the second month of growth the negative impact of reduced irrigation was evident with three times watering every week having better seedling responses. Specifically, those seedlings had greater root growth potential; a characteristic that relates with increased transplanting success. Therefore, based on the results of the study, the species of Myrtus Communis can cope with adverse drought growth conditions as reflected by low irrigation frequency (one watering every two weeks) for a period of one month. Nonetheless, by the end the second experimental month, watering three times every week resulted in better growth responses while the species indicated avoidance mechanisms (e.g. leaf abscission) that enabled the species to cope with drought conditions.